Detection of Clinically Relevant Copy Number Variation of SEZ6L2 Gene in a Bangladeshi Autism Spectrum Disorder Cohort - Uddin, KM Furkan; Amin, Md Robed; Sultana, Nasima; Aleem, Md Abdul; Sarker, Suprovath Kumar; Banu, Laila Anjuman; Ali, Mohammad Shaheb; Khanam, Wahida; Rahman, Narsis; Baqui, Md Abdul; et al. (Bangladesh Journal of Medicine, 2019)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder. Due to long term impairment, high genetic component (heritability> 90%), lack of effective prevention and treatment, ASD has been prioritized for genetic studies. Studies on Copy Number Variations (CNV) at chromosome 16p11.2 locus have mostly been conducted in population of pure or predominant European ancestry. It is not known whether this is also prevalent among the ASD affected individuals in population of other ancestries such as Bangladeshi population. The aim of this research work is to detect CNV of SEZ6L2 gene at 16p11.2 locus and to describe the associated clinical characteristics in Bangladeshi cohort with clinically diagnosed ASD. Methods: The known SEZ6L2 gene was interrogated for copy number variation (CNV) in twenty five autistic patients with SYBR Green I assay using the real time qPCR. Probands were interrogated using relative standard curve (efficiency correction) method. Epilepsy with speech disorder and postnatal infection might be more common among autistic patients with CNV at this SEZ6L2 gene. Results: The two cases with characteristics CNV was detected who had clinically manifestation of convulsion at different ages, partial developmental delay in multiple domains including delay in walking, speech delay and mental age not corresponding with the chronological age. This work describes the frequency of CNV is 8.3 %. This rate is skewed due to small sample size and do not reflect the true frequency of 16p11.2 duplication impacting SEZ6L2 gene. Conclusion: Epilepsy with speech disorder and postnatal infection might be more common among autistic patients with CNV at this SEZ6L2 gene. Bangladesh J Medicine Jan 2019; 30(1) : 24-29